Over the shop - Lawson, JonArno (Candlewick Press, 2021)
"A lonely little girl and her grandparent need to fill the run-down apartment in their building. But taking over the quarters above their store will mean major renovations for the new occupants, and none of the potential renters can envision the possibilities of the space--until one special couple shows up. With their ingenuity, the little girl's big heart, and heaps of hard work, the desperate fixer-upper begins to change in lovely and surprising ways"--Provided by publisher.